PANHER study: a 20-year treatment outcome analysis from a multicentre observational study of HER2-positive advanced breast cancer patients from the real-world setting. (November 2021) - Pizzuti, Laura; Krasniqi, Eriseld; Sperduti, Isabella; Barba, Maddalena; Gamucci, Teresa; Mauri, Maria; Veltri, Enzo Maria; Meattini, Icro; Berardi, Rossana; Di Lisa, Francesca Sofia; Natoli, Clara; Pistelli, Mirco; et al.
Background: The evolution of therapeutic landscape of human epidermal growth factor receptor-2 (HER2)-positive breast cancer (BC) has led to an unprecedented outcome improvement, even if the optimal sequence strategy is still debated. To address this issue and to provide a picture of the advancement of anti-HER2 treatments, we performed a large, multicenter, retrospective study of HER2-positive BC patients. Methods: The observational PANHER study included 1, 328 HER2-positive advanced BC patients treated with HER2 blocking agents since June 2000 throughout July 2020. Endpoints of efficacy were progression-free survival (PFS) and overall survival (OS). Results: Patients who received a first-line pertuzumab-based regimen showed better PFS ( p < 0.0001) and OS ( p = 0.004) than those receiving other treatments. Median PFS and mOS from second-line starting were 8 and 28 months, without significant differences among various regimens. Pertuzumab-pretreated patients showed a mPFS and a mOS from second-line starting not significantly affected by type of second line, that is, T-DM1 or lapatinib/capecitabine ( p = 0.80 and p = 0.45, respectively). Conversely, pertuzumab-naïve patients receiving second-line T-DM1 showed a significantly higher mPFS compared with that of patients treated with lapatinib/capecitabine ( p = 0.004). Median OS from metastatic disease diagnosis was higher in patients treated with trastuzumab-based first line followed by second-line T-DM1 in comparison to pertuzumab-based first-line and second-line T-DM1 ( p = 0.003), although these data might be partially influenced by more favorable prognostic characteristics of patients in the pre-pertuzumab era . No significant differences emerged when comparing patients treated with 'old' or 'new' drugs ( p = 0.43), even though differences in the length of the follow-up between the two cohorts should be taken into account. Conclusion: Our results confirmed a relevant impact of first-line pertuzumab-based treatment and showed lower efficacy of second-line T-DM1 in trastuzumab/pertuzumab pretreated, as compared with pertuzumab-naïve patients. Our findings may help delineate a more appropriate therapeutic strategy in HER2-positive metastatic BC. Prospective randomized trials addressing this topic are awaited.